Risk on Consumer Finance Company Personal Loans - Benston, George J. (Journal of Finance, 1977)
George J. Benston, Risk on Consumer Finance Company Personal Loans, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 593-607